Loneliness and Anxiousness as Predictors of Facebook use among College Students - M. Langgaman, Aleli (International Journal of English Literature and Social Sciences (IJELS), 2021)
Social Networking Sites (SNS), such as Facebook, have been attracting so many users worldwide by offering virtual communications to its users. Thus, the study examined if loneliness and anxiousness would predict Facebook use among college students. A survey of 365 participants who are active Facebook users was conducted at Kalinga State University. The study examined the predictor variables: loneliness and anxiousness in relation to the Facebook Intensity Scale (Ellison et al. 2007). The two predictor variables were examined using a linear regression model and results showed that college students have moderate levels of loneliness, anxiousness and Facebook use. Furthermore, loneliness has a weak positive relationship with Facebook use while anxiousness has no relationship with Facebook use. Lastly, it was also found that loneliness contributes to Facebook use among college students. The study adds to the increasing body of literature investigating why individuals develop an emotional attachment to Facebook and the precursors of why people are drawn to connect in Facebook.